PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BIT MERAH (Beta vulgaris L.) DENGAN SISTEM POTTING - Efita Febriana; Nora Augustien Kusumaningrum; Makhziah Makhziah (Plumula : Berkala Ilmiah Agroteknologi, 2020)
Red Beet (Beta vulgaris L.) is one of plant that are benefical to health. The purpose of this study was to determine the composition of the planting media and the concentration of liquid organic fertilizer that is appropriate for increasing growth and production of red beet plants. The study was conducted at the Greenhouse of the Faculty of Agriculture UPN "Veteran" East Java in December 2019 to March 2020. The research was a factorial experiment using a Completely Randomized Design (CRD) consisting of 2 factors and was repeated 3 times. The first factor is the composition of the planting media (M) and the second factor is the concentration of liquid organic fertilizer (P). Data were analyzed with ANOVA, if it had significant effect, it was continued with BNJ 5%. The treatment of the composition of the planting medium did not significantly affect all parameters of the observation, whereas the treatment of liquid organic fertilizer concentration significantly affected the observation parameters of plant lengths of 21, 28 and 35 hst, tuber weights and the wet weight of the stover of underground plants where the concentration of 6 ml/L gives the best results on red beet tubers.